Arno Geigers Es geht uns gut aus der Sicht des zeitgenössischen Familien- und Generationsromans - Bryk, Maria (Acta neophilologica, 2009)
This essay presents Arno Geiger's family novel Es geht uns gut (2007) as an example of a literary genre, which becomes more and more popular. A family/generation novel has had its peak popularity in the first half of the 20th century. The purpose of this essay is though to characterise the genre in its recent form and to prove the genre is still alive. One of the possible explanations to the present interest in a family novel is its versatility and the potential for raising and combining of multiple, various up-to-date subjects. Family and generation conflicts are the main motive of this genre, often, as in Geiger's novel, against a background of historical problems. For German family novels this historical setting is particularly Nazism. A family/generation novel does not though aim to present the "historical truth" in an objective way but rather presents the past in a way it has been internalised by family remembrance. This way any negative episodes are often dislodged or neutralized. Another motive widely taken up by Geiger, is social and moral transformation of female characters struggling to change their situation in society. The essay discusses also the traditional genre motive -the rise and fall of a family. Geiger's book is an interesting example of a modern family/generation novel. It refers to the classical genre and takes up typical motives but at the same time it is distinguished by its different, fresh approach.
Keywords: avstrijska književnost; avstrijski roman; Geiger, Arno, 1968-; Geiger, Arno: Es geht uns gut; generacijski roman; German-language literature; literarne študije; nemška književnost; sodobni roman